Effect of Online Customer Review, Online Customer Rating, Online Trust, and Price on Interest to Buy Marketplace in Indonesia - Naomi, Intan Prilia; Ardhiyansyah, Andri (Master of Management Diponegoro University, 2022)
The rapid development and progress of the internet have led to a shift in consumer behavior, namely, consumers who are starting to be interested in shopping online. The difference lies in the ability of consumers to assess the products they are interested in purchasing decisions. For that, we need to determine what factors can influence consumer buying interest so that it can cause the phenomenon of increasing online shopping trends in Indonesia, especially in terms of online customer review variables, online customer ratings, trust, and prices. This research is quantitative research with a survey method. The population in this study were all online marketplace users in Indonesia, and the sampling technique used purposive sampling with a total sample of 210 respondents. The data collection technique used an online questionnaire that the instrument had tested. The data analysis technique used to answer the hypothesis is partial and simultaneous testing with the help of multiple regression using the Software Statistical Product and Service Solution (SPSS 25. The findings in this study note that online customer reviews, online customer ratings, online trust, and prices have a positive and significant effect on buying interest in the marketplace in Indonesia, either partially or simultaneously.